2016
DOI: 10.1002/cphc.201601056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Liquid Medium and Ablation Wavelength on the Properties of Cadmium Sulfide Nanoparticles Formed by Pulsed‐Laser Ablation

Abstract: Pulsed-laser ablation in liquid (PLAL) is a green synthesis technique to obtain semiconductor nanomaterials in colloidal form. Herein, cadmium sulfide (CdS) nanoparticles were synthesized by the pulsed-laser ablation of a CdS target in different liquid media by using λ=532 and 1064 nm outputs from a pulsed (10 ns, 10 Hz) Nd:YAG laser at different ablation fluence values. The morphology, structure, crystalline phase, elemental composition, optical, and luminescent properties of CdS nanomaterials were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…It is worth mentioning that such graphitic shells are formed on NPs synthesized using metal targets in certain organic liquids such as toluene [36,40] and dimethyl sulfoxide (DMSO). [42] Interestingly, such shell formation is absent in ZnO and CdS NPs synthesized using ZnO [43] and CdS [44] targets. [41] It is reported that the aromatic debris from these solvents acts as a carbon source for graphitization of carbon which leads to the shell formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is worth mentioning that such graphitic shells are formed on NPs synthesized using metal targets in certain organic liquids such as toluene [36,40] and dimethyl sulfoxide (DMSO). [42] Interestingly, such shell formation is absent in ZnO and CdS NPs synthesized using ZnO [43] and CdS [44] targets. [41] It is reported that the aromatic debris from these solvents acts as a carbon source for graphitization of carbon which leads to the shell formation.…”
Section: Resultsmentioning
confidence: 99%
“…[41] It is reported that the aromatic debris from these solvents acts as a carbon source for graphitization of carbon which leads to the shell formation. [42] Interestingly, such shell formation is absent in ZnO and CdS NPs synthesized using ZnO [43] and CdS [44] targets. Therefore, several factors influence the formation of graphitic shells on the synthesized NPs in liquid using LAL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, inability of controlling the atomic density and temperature gradient in the plasma results in formation of particles with different sizes and shapes. More details on the role of liquid media in determining the particle morphologies by PLAL are available in literature ,…”
Section: Resultsmentioning
confidence: 99%